Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-39 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
A-C. Volitional abduction and adduction of the toes becomes possible again in the SCI patient Nefeli. With the activation of the Mm. interrossei dorsales and plantares (C), the regeneration of the spinal cord has reached the S1 to S3 spinal cord segments.